Challenges for implementing project planning in the NGO sector in the Overberg Municipality - Buyani, Nomathemba (University of the Western Cape, 2016)
Magister Artium (Social Work) - MA(SW) === Non-Governmental Organisations (NGOs) played a vital role in the history of the welfare sector in South Africa and are working alongside the government sector to combat social ills. The role of the NGO sector is to ensure the provision of a comprehensive network of social development services that enable and empower the poor, the vulnerable, and those with special needs. The ongoing financial shortages from NGOs were a growing concern for all the stakeholders in the welfare sector. The goal of this study was therefore to explore and describe the challenges in implementing project planning in the NGO sector. This study followed a qualitative research approach and used exploratory and descriptive research designs. Participants were purposely selected from the various NGOs in the Overberg Municipality. The data collection took place in focus group discussions and individual interviews with the aid of an interview guide. Data was analysed according to the eight steps of Tesch (in Creswell, 2003). Findings were verified according to Guba’s (1981) model of trustworthiness based on the criteria identified in Krefting (1991). The findings that were generated during the research study indicated that challenges for implementing project planning in the NGO sector had an impact on their service delivery. An enabling factor for implementing project planning and the writing of business plans was the fact that training in project management assisted project managers to market their services and permitted supervisors to fulfil different roles. The second theme that emerged from the study was disenabling factors or problems facing the planning and writing of the business plan. It demonstrated a lack of knowledge among social workers who lacked those skills and coordination and planning amongst NGO in the same area. The implementation of a basket of services influenced project outcomes, lack of resources and infrastructure for implementation of projects. The third theme that emerged from the study was stakeholders’ influence in project implementation and the influence on efficient and effective project outcomes. It included social work goals versus client goals, the relationship between the board members of the NGOs and social workers, the relationship between the Department of Social Development and social workers in the NGO sector, and relationships between the social workers and their supervisors. Recommendations included short- and long-term recommendations. It was concluded that NGOs experience challenges with regard to implementation of project planning.